Evaluación de dos sistemas de siembras y densidades poblacionales en el cultivo de Plátano cv Barraganete (Musa x paradisiaca AAB). - Pisco Pisco, Jacinto Daniel (2018)
The plantain sector in Ecuador has been increasing over the years, the export of this fruit is increasing, thus providing a source of income for farmers which implement sowing systems with high population densities. For this reason, the following research was proposed with the objective of evaluating the yield of Banana cv Barraganete clusters, using two sowing systems and two population densities. In the Tropical Pichilingue station (INIAP) located at Km. 5 via Quevedo - El Empalme, the effect of two sowing systems and population densities in the plantain Barraganete crop was evaluated. In the investigation used Barraganete plants obtained from a nursery with an age of 3 months were detected, 4 treatments with 4 repetitions were studied, the factors to be evaluated were factor A (Planting systems, single row, double row) and factor B (Planting densities 1,333 plants/ha-1 and 2,500 plants/ha-1), the Completely Random Experimental Design (DCA) was used with factorial arrangement A x B, with homogeneous material and without division in the plots. From the results obtained in the use of two sowing systems and population densities, treatment double row 2,500 plants/ha-1 registered the highest yield with 1,001.15 boxes/ha-1, treatment single row 2,500 plants/ha-1 874.48 boxes/ha, treatment double row 1,333 plants/ha-1 559.19 boxes/ha and treatment single row 1,333 plants/ha-1 had the lowest yield with 461 boxes/ha-1. Having carried out the economic analysis of the treatments, the study determined that the highest yield was presented at densities of 2,500 plants/ha-1, the treatment double row 2,500 plants/ha-1 reached the highest marginal utility with $ 4,760. 48 dollars, the treatment single row 2,500 plants/ha-1 obtained a marginal profit of $ 3,312.22 dollars, in the densities of 1,333 plants/ha-1, the treatment double row 1,333 plants/ha-1 presented the highest marginal utility with $ 1,106.71 dollars, the treatment single row 1,333 plants/ha considered as the control presented values below the other treatments. Keywords: Barraganete, population densities, planting systems, phenological.